Quantifying Costs of Drought Risk in Ethiopia : A Technical Note - Drechsler, Mareile; Coll-Black, Sara; Tatin-Jaleran, Clemence; Clarke, Daniel (World Bank, Washington, DC, 2020)
Ethiopia’s ministry of finance and economic cooperation (MoFEC) has requested that the World Bank and the United Kingdom (UK) Department for International Development (DfID) provide technical assistance to MoFEC to develop a comprehensive disaster risk financing framework for Ethiopia, in support of Government of Ethiopia (GoE’s) interest in continuing to strengthen its system for delivery of post-disaster aid. MoFEC has requested that the analysis identify sources of funding for past humanitarian response and include a forward-looking analysis using statistical simulation techniques, taking into account historical changes in population and vulnerability. This document represents an effort to quantify the historical needs and expenditures associated with drought risks, with a view to supporting the dialogue about ways to strengthen Ethiopia’s existing risk financing framework by improving the cost-effectiveness of risk management instruments used, and timeliness of response. The report is structured as follows: section one provides an analysis of the historic needs and expenditures associated with droughts in Ethiopia. Section two provides a forward-looking statistical analysis of disaster risks, identifying the annual financial needs associated with disasters, as well as a probabilistic analysis of the costs associated with disasters of different frequency and severity. Section three presents a way to view the financial gap between the current sources of financing for drought risks and expected annual losses related to droughts. Section four concludes.